Fragility, Conflict, and Migration - Kosec, Katrina; Läderach, Peter R.D.; Ruckstuhl, Sandra (CGIAR System Organization, 2023)
Fragility, Conflict, and Migration addresses challenges to livelihood, food, and climate security faced by some of the most vulnerable populations worldwide. The Initiative focuses on building climate resilience, promoting gender equity, and fostering social inclusion. It forms part of CGIAR’s new Research Portfolio, delivering science and innovation to transform food, land, and water systems in a climate crisis.